Impact of high-frequency ultrasound on nanocomposite microcapsules: in silico and in situ visualization. Issue 4 (8th December 2015) - Korolovych, V. F.; Grishina, O. A.; Inozemtseva, O. A.; Selifonov, A. V.; Bratashov, D. N.; Suchkov, S. G.; Bulavin, L. A.; Glukhova, O. E.; Sukhorukov, G. B.; Gorin, D. A.
Abstract : Simulation and direct visualization of high-frequency (1.2 MHz) ultrasound impact on microcapsules with ZnO nanoparticles embedded in the shell. Abstract : The impact of high-frequency (1.2 MHz) ultrasound with a power density of 0.33 W cm −2 on microcapsule nanocomposite shells with embedded zinc oxide nanoparticles was investigated by exploring modeling simulations and direct visualization. For the first time the sonication effect has been monitored in situ on individual microcapsules upon exposure of their aqueous suspension to ultrasound. The stress distribution on the microcapsule shell for the impact of ultrasound with high (1.2 MHz) and low (20 kHz) frequency at two fixed intensities (0.33 and 30 W cm −2 ) has been modeled. As shown in silico and experimentally the nanocomposite microcapsules were destroyed more effectively by the action of high-frequency (1.2 MHz) ultrasound in comparison to the low frequency (20 kHz) one with the same power density.